OPTIMALISASI ETOS KERJA GURU SMK JAKARTA BARAT MELALUI BUDAYA ORGANISASI DAN KECERDASAN EMOSIONAL - Euis Nessia Fitri; Dani Rahman Hakim (Universitas Kuningan, 2020)
ABSTRACTThis study aims to analizing the effect of organization culture and emotionalintelligence of teachers on work ethic in vocational high school teacher at thewest Jakarta. Research method is quantitative with multiple regression. Researchmethode is quantitative approach with regression analisys to proving the theorywhich is basis of the research hypotesys. Collecting data method is used thequestionnaire with sample of 135 vocational teacher in public and private schoolof West Jakarta. Result of this research indicate that organizational culture andemotional intelligence significantly influencing the work ethic. Based on thatresult, vocational school management shoud be able to build an effectiveorganizational culture and provide emotional spiritual questions (ESQ) trainingto the teacher in order to improve their work ethic.Keyword : Emotional_Intelligence, Organizational_Culture, Work_Ethic